Variation and prevalence characteristics of influenza in Giuzhou province, 2011 - 2021 - Qin-ni ZHENG; Li-juan REN; Li ZHUANG (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To analyze prevalence characteristics and variation trend of influenza in Guizhou province during 2011- 2021 and to provide evidences for influenza prevention and control. Methods Throat swab specimens were collected from influenza-like illness (ILI) cases at fever/internal medicine and pediatric clinics of 13 national influenza sentinel surveillance hospitals in Guizhou province during 2011 - 2021 and detected with real-time reverse transcription-polymerase chain reaction (RT-PCR). Statistical analysis was conducted on the basis of annual influenza seasons. ResultsOf the 135 537 specimens detected during the 10-year period, 16.73% (22 676) were positive for influenza virus nucleic acid. Among the positive specimens, the detection rate was the highest (34.3%) for subtype of H3N2 and the lowest (13.69%) for subtype of BY. Various viral subtypes were prevalent alternately during the period. Two prevalence peaks of influenza virus infection in winter-spring season and in summer season were observed, with slightly more infectious cases among females than among males and more cases among the people aged 5 - 24 years. There was a subtype-specific difference in the susceptibility of influenza virus in various populations and there was a significant difference in annual positive rate for the specimens detected. ConclusionDuring 2011 - 2021 in Guizhou province, influenza was prevalence periodically with alternative prevalent viral subtypes; more influenza infections occurred in winter-spring and in summer seasons, especially among young people. The results suggest that surveillance and analysis on viral strain variation timely should be strengthened.